2014
DOI: 10.1186/s13568-014-0078-z
|View full text |Cite
|
Sign up to set email alerts
|

Paracentrin 1, a synthetic antimicrobial peptide from the sea-urchin Paracentrotus lividus, interferes with staphylococcal and Pseudomonas aeruginosa biofilm formation

Abstract: The rise of antibiotic-resistance as well as the reduction of investments by pharmaceutical companies in the development of new antibiotics have stimulated the investigation for alternative strategies to conventional antibiotics. Many antimicrobial peptides show a high specificity for prokaryotes and a low toxicity for eukaryotic cells and, due to their mode of action the development of resistance is considered unlikely. We recently characterized an antimicrobial peptide that was called Paracentrin 1 from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 59 publications
2
14
0
1
Order By: Relevance
“…On the other hand, residue K 7 is in a random coil conformation in the first stable conformation, due to the position of this amino acid in the centre of the loop. Similar results were recently obtained with the analogue fragment, SP1, from sea-urchin (Schillaci et al 2014).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, residue K 7 is in a random coil conformation in the first stable conformation, due to the position of this amino acid in the centre of the loop. Similar results were recently obtained with the analogue fragment, SP1, from sea-urchin (Schillaci et al 2014).…”
Section: Resultssupporting
confidence: 89%
“…Most of known AMPs, have a cationic amphiphilic alpha-helical structure and they are able to target the cytoplasmic membrane and to provoke cell death by osmotic shock (Di Luca et al 2014). As previously described, also the peptide SP1 from the sea urchin P.lividus has a hydrophobic region of three non polar residues and cationic and polar residues at both ends, which renders the peptide soluble in aqueous solution and provide a binding site for bacterial membranes (Schillaci et al 2014). These structural features differently from most AMPs, are designed as transmembrane mimetic models (Chan et al 2004;Liu and Deber 1998;Stark et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the molecular mechanism underlying Enterococcus resistance to L12 requires further investigation in future studies. The MIC of L12 against S. aureus was similar to traditional antibacterial drugs, and the antibacterial activity of L12 was comparable with other AMPs (22)(23)(24)(25). Furthermore, the MICs of L12 exhibited no correlation with resistance to the tested antibiotics, the strains resistant to more antibiotics were not more resistant to L12, which suggested that L12 may be used to treat infections caused by MRSA strains.…”
Section: Discussionmentioning
confidence: 83%
“…In particular, we focused on the smallest 11 amino acid peptide (9–19), whose molecular weight was 1251.7, that we called Paracentrin 1 (SP1, EVASFDKSKLK). We demonstrated a broad range of activity against planktonic and biofilm forms of representative pathogens, like staphylococcal strains and P. aeruginosa, but we found Minimum Inhibitory Concentration (IC)values in the order of mg/mL [ 10 ]. Subsequently, we compared the amino acid sequence of SP1 with the corresponding fragment 9–19 (EIEKFDKSKLK) of human thymosin β4 (Tβ4).…”
Section: Introductionmentioning
confidence: 99%